2016
DOI: 10.1371/journal.pone.0152084
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Receiving Education on Venous Thromboembolism Prevention – A Survey of Stakeholder Organizations

Abstract: ImportanceVenous thromboembolism (VTE) is a major cause of morbidity and mortality among hospitalized patients and is largely preventable. Strategies to decrease the burden of VTE have focused on improving clinicians’ prescribing of prophylaxis with relatively less emphasis on patient education.ObjectiveTo develop a patient-centered approach to education of patients and their families on VTE: including importance, risk factors, and benefit/harm of VTE prophylaxis in hospital settings.Design, Setting and Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 28 publications
(23 reference statements)
0
42
0
2
Order By: Relevance
“…A set of 56 records identified from electronic database searches was selected for inclusion, and 3 additional studies [80][81][82] were identified by checking references included in a previously published guideline on the same topic. 83 Overall, we included 44 quantitative studies, [55][56][57][58][59][60][61][62][63][64][65][80][81][82] 14 qualitative studies, [66][67][68][69][70][71][72][73][74][75][76][77][78][79] and 1 study with both types of evidence 54 (Figure 1). Fourteen of the included studies reported patients' values or utilities, [24][25][26][27][28][29][30][31][32][33][34][35][36][37] 34 nonutility studies use...…”
Section: Searchesmentioning
confidence: 99%
See 1 more Smart Citation
“…A set of 56 records identified from electronic database searches was selected for inclusion, and 3 additional studies [80][81][82] were identified by checking references included in a previously published guideline on the same topic. 83 Overall, we included 44 quantitative studies, [55][56][57][58][59][60][61][62][63][64][65][80][81][82] 14 qualitative studies, [66][67][68][69][70][71][72][73][74][75][76][77][78][79] and 1 study with both types of evidence 54 (Figure 1). Fourteen of the included studies reported patients' values or utilities, [24][25][26][27][28][29][30][31][32][33][34][35][36][37] 34 nonutility studies use...…”
Section: Searchesmentioning
confidence: 99%
“…41,42,49,50,[52][53][54][55][56][57]59,60,[62][63][64]82 Six of those studies evaluated the preference for injections or oral administration routes in 1645 medical or surgical patients receiving prophylaxis. 49,55,56,60,62,64 There was a clear preference for oral medication (range, 60-86% of patients) over subcutaneous injection, because it is easier to take and to integrate into the daily routine, and it is also perceived as less painful and less expensive. For participants preferring the injection route, the stated reasons for the preferences included faster onset of action, avoidance of pill burden, and ease of use (1645 participants from 6 studies; moderate certainty).…”
Section: ⊕⊕⊕○mentioning
confidence: 99%
“…Using a modified Delphi method, we engaged patient stakeholders from the 4 collaborating organizations to build consensus on patient‐centered VTE education methods. Input from this Delphi assessment was used to build educational materials including paper brochures published in 8 different languages and a 10‐minute educational video filmed by an Oscar‐winning documentary director featuring both clinicians and patients relating their VTE experience and the importance of VTE prevention . These educational materials are available for public use (http://www.hopkinsmedicine.org/armstrong_institute/improvement_projects/VTE/) and are being used in a trial of a patient‐centered intervention bundle to reduce rates of VTE prophylaxis nonadministration.…”
Section: Patient‐centered Approaches To Improve Vte Prophylaxis Adminmentioning
confidence: 99%
“…Input from this Delphi assessment was used to build educational materials including paper brochures published in 8 different languages and a 10-minute educational video filmed by an Oscar-winning documentary director featuring both clinicians and patients relating their VTE experience and the importance of VTE prevention. 24 These educational materials are available for public use (http://www.hopkinsmedicine.org/arm-strong_institute/improvement_projects/VTE/) and are being used in a trial of a patient-centered intervention bundle to reduce rates of VTE prophylaxis nonadministration. We also conducted a cluster-randomized trial to compare different approaches to nurse education (https://clinicaltrials.gov/ct2/show/NCT02301793).…”
Section: Patient-centered Approaches To Improve Vte Prophylaxis Adminmentioning
confidence: 99%
“…This is consistent with Arab culture, [29] in which doctors in most of the time are ranked at the top with respect to authority and knowledge related to healthcare issues. Similarly, Popoola [30] found that 84% of the participants in their study would like to receive education about their health issues by talking to a physician. Noticeably, the findings of the current study indicated that social media has a potential contribution in patients' education about antibiotics use, though participants preferred other means of receiving education.…”
Section: Discussionmentioning
confidence: 93%